The fragility of an independent judiciary: Lessons from Hungary and Poland–and the European Union - Kriszta Kovács; Kim Lane Scheppele (Communist and Post-Communist Studies, 2018)
When the European Union was founded, it was assumed that all Member States admitted as consolidated democracies would maintain their constitutional commitments. In recent years, Hungary and Poland have challenged this premise as elected autocratic governments in those countries have captured independent institutions and threatened long-term democracy. The judiciaries of these countries have been hard hit. In this paper, we trace what has happened to the judiciaries in Hungary and Poland, showing how first the constitutional courts and then the ordinary judiciary have been brought under the control of political forces so that there is no longer a separation of law and politics. We also explore why the European Union has so far not been able to stop this process. In the end, the European judiciary, particularly the Court of Justice, is attempting a rescue of national judiciaries, but the results are so far unclear.
Keywords: 330; comparative constitutional law; judicial independence; Hungary; Poland; European Union; democratic decline